Spreading depolarisations and outcome after traumatic brain injury: a prospective observational study - Hartings, Jed A.; Bullock, M Ross; Okonkwo, David O; Murray, Lilian S; Murray, Gordon D; Fabricius, Martin; Maas, Andrew IR; Woitzik, Johannes; Sakowitz, Oliver; Mathern, Bruce; Roozenbeek, Bob; Lingsma, Hester; et al. (The lancet, 2011)
Background - Pathological waves of spreading mass neuronal depolarisation arise repeatedly in injured, but potentially salvageable, grey matter in 50-60% of patients after traumatic brain injury (TBI). We aimed to ascertain whether spreading depolarisations are independently associated with unfavourable neurological outcome. - Methods - We did a prospective, observational, multicentre study at seven neurological centres. We enrolled 109 adults who needed neurosurgery for acute TBI. Spreading depolarisations were monitored by electrocorticography during intensive care and were classified as cortical spreading depression (CSD) if they took place in spontaneously active cortex or as isoelectric spreading depolarisation (ISD) if they took place in isoelectric cortex. Investigators who treated patients and assessed outcome were masked to electrocorticographic results. Scores on the extended Glasgow outcome scale at 6 months were fitted to a multivariate model by ordinal regression. Prognostic score (based on variables at admission, as validated by the IMPACT studies) and spreading depolarisation category (none, CSD only, or at least one ISD) were assessed as outcome predictors. - Findings - Six individuals were excluded because of poor-quality electrocorticography. A total of 1328 spreading depolarisations arose in 58 (56%) patients. In 38 participants, all spreading depolarisations were classified as CSD; 20 patients had at least one ISD. By multivariate analysis, both prognostic score (p=0·0009) and spreading depolarisation category (p=0·0008) were significant predictors of neurological outcome. CSD and ISD were associated with an increased risk of unfavourable outcome (common odds ratios 1·56 [95% CI 0·72-3·37] and 7·58 [2·64-21·8], respectively). Addition of depolarisation category to the regression model increased the proportion of variance in outcome that could be attributed to predictors from 9% to 22%, compared with the prognostic score alone. - Interpretation - Spreading depolarisations were associated with unfavourable outcome, after controlling for conventional prognostic variables. The possibility that spreading depolarisations have adverse effects on the traumatically injured brain, and therefore might be a target in the treatment of TBI, deserves further research. - Funding - US Army CDMRP PH/TBI research programme.
Gesehen am 03.08.2022